Growth parameters and mortality rates of the blue swimming crab, Portunus segnis (Forskal, 1775) in coastal waters of Persian Gulf and Gulf of Oman, Iran - Safaie, Mohsen; Kiabi, Bahram; Pazooki, Jamileh; Shokri, Mohammad Reza (Indian Journal of Fisheries, 2013)
Population parameters of the blue swimming crab, Portunus segnis in coastal waters of the Persian Gulf and the Gulf of Oman (Hormozgan Province) were estimated using the swept area method. Sampling was carried out monthly from May 2010 to October 2011. The carapace width and weight relationship demonstrated that growth in both sexes is allometric (p